2008
DOI: 10.4103/0256-4947.51703
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal diagnosis, prevalence and outcome of major congenital anomalies in Saudi Arabia : A hospital-based study

Abstract: BACKGROUND AND OBJECTIVESThe exact antenatal prevalence of congenital anomalies in Saudi society is unknown. Early antenatal diagnosis of congenital anomalies is crucial for early counselling, intervention and possible fetal therapy. The objective of this study was to evaluate the antenatal frequency of major congenital anomalies and malformation patterns in our hospital population and to evaluate the outcome and perinatal mortality rates for major congenital anomalies.PATIENTS AND METHODSThis was a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 5 publications
4
23
1
Order By: Relevance
“…Similar findings were found in a Saudi Arabian study on antenatal prevalence of congenital anomalies which showed a median gestational age at diagnosis of 31 weeks [10]. In contrast, the Eurofetus study showed a mean gestational age at diagnosis of 24.2 weeks likely due to the differing health care system and health-seeking behavior in Europe [14].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar findings were found in a Saudi Arabian study on antenatal prevalence of congenital anomalies which showed a median gestational age at diagnosis of 31 weeks [10]. In contrast, the Eurofetus study showed a mean gestational age at diagnosis of 24.2 weeks likely due to the differing health care system and health-seeking behavior in Europe [14].…”
Section: Discussionsupporting
confidence: 74%
“…A further study done in Madina Teaching Hospital, Faisalabad on grayscale ultrasound showed a comparable antenatal prevalence of 2.97% [9]. Another similar Saudi Arabian study produced a figure of 2.79% [10]. …”
Section: Discussionmentioning
confidence: 98%
“…This rate in a study in Saudi Arabia was 34.9% (11). The mortality rate in our study was greater than the rate reported by studies in Turkey (14% -15.5%) (17,29) and Denmark (1.61%) (43) and less than the rate reported by studies conducted in Birjand (78%) (23) and Libya (49.1%) (18).…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, a study in Saudi Arabia showed that 66.6% of major CAs were isolated and 33.4% were multiple. The most common CAs in Saudi Arabia were urinary (11,28) and cranial anomalies (11). A study in Turkey also reported that 76% of CAs were isolated and 24% of them were multiple (29).…”
Section: Discussionmentioning
confidence: 99%
“…Salute et al . [8] showed that genitourinary anomalies were the most common fetal anomalies diagnosed in the antenatal period constituting 38.6% of all anomalies diagnosed in that center. However, the prevalence and pattern of CAKUT was not reported.…”
Section: Discussionmentioning
confidence: 99%